SYNTHESIS OF NOVEL CHALCONES OF SCHIFF’S BASES AND TO STUDY THEIR EFFECT ON BOVINE SERUM ALBUMIN - Garg , Shweta; Raghav, Neera (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: Some novel chalcones consisting â€“unsaturated carbonyl group and C=N bond were synthesized i.e. 1-(4-(benzylideneamino)phenyl)-3-phenylprop-2-en-1-ones and studied the influence of theirÂ presence on bovine serum albumin. Methods: 1-(4-(benzylideneamino)phenyl)-3-phenylprop-2-en-1-ones were synthesized by the reaction of substituted benzaldehydes with 1-((4-benzylideneamino)phenyl)ethanone and in the presence of a base. The structures were confirmed by their IR and 1HNMR spectra. After establishing the structures of 1-(4-(benzylideneamino)phenyl)-3-phenylprop-2-en-1-ones, their effect were observed on BSA in solution. Results: Out of synthesized chalcones, 1-(4-(4-(3-phenylallylideneamino)phenyl)-3-p-tolylprop-2-en-1-one is most reactive chalcone as it decreased the availability of BSA in solution to maximum extent. Conclusion: 1-(4-(benzylideneamino)phenyl)-3-phenylprop-2-en-1-ones interact with the bovine serum albumin which is responsible for the transportation of a number of compounds. Keywords: Bovine serum albumin, interaction studies, chalcones.